Cloud Computing Benefit Realisation in a South African Public Sector: A postadoption study - Breda, Leigh N (Department of Information Systems, 2023)
Background: Cloud Computing is a globally evolving trend that is changing the landscape of Information Technology as we know it. The perceived benefits of Cloud adoption are spurring IT leaders to move to Cloud Computing to maintain the competitive edge, regardless of some of the challenges associated with Cloud adoption. Currently, the predominant reason for organisations to adopt Cloud Computing is the reduction of costs. However, some organisations report that they are not receiving the perceived benefits as expected pre-adoption. Despite this known fact that cost reduction is not guaranteed, organisations are expected to increase their IT spending in the future on Cloud Computing. As organisations are reporting that they are not receiving a tangible and easily measurable benefit such as cost reduction, it is imperative for organisations to measure and confirm that intangible benefits which are difficult to quantify are being received. This measured approach is essential to aid organisations in understanding the actualised benefits of Cloud Computing. Objective: Current literature predominantly focuses on the adoption of Cloud Computing with the private sector as its consumers. Minimal research has been explored with Cloud Computing postadoption, explicitly focusing on the South African public sector context. Little is known about these organisations and if they have actualised the perceived benefits from its adoption phase. Further to this, understand how these organisations have measured the degree in which they have benefited from the adoption. The purpose of this research is to contribute to knowledge regarding organisations in the public sector and what factors influence the actualisation of perceived adoption benefits postimplementation. Method: The researcher adopted a constructivism ontological stance, interpretivist epistemology, and an inductive approach to conduct this research. Qualitative data was collected in the form of 20 semistructured interviews conducted over a period of 12 months. These interviews were conducted in an organisation in the public sector that has implemented Cloud solutions already, and can provide a retrospective view of its adoption. Thematic analysis was utilised to sort the responses into categories and themes. These themes were further filtered by using a research model based on the TOE framework as the lens to structure the data. Findings: This research revealed a discrepancy in the perceived benefits of pre-adoption and the received actualised benefits of post-adoption across the organisation. This is primarily due to the lack of IT management predefining metrics to determine the degree that the adoption has benefited the organisation. Secondly, depending on the type of Cloud service and user role, benefits can vary, thus having one part of the organisation very satisfied and another area dissatisfied. Lastly, the pre-adoption factor for adoption is not necessarily a factor that influences the continued use of Cloud Computing. External factors such as the COVID-19 pandemic have shifted perceptions and organisational requirements due to the increased pressure to deliver services and work remotely. This increase in dependency on Cloud Computing altered the main factor of cost reduction, so significantly that if the Cloud would cost more, the organisation would continue its use due to the additional benefits that Cloud Computing provides.